Influence of host iron status on Plasmodium falciparum infection - Clark, Martha A.; Goheen, Morgan M.; Cerami, Carla (Frontiers in Pharmacology, 2014)
Iron deficiency affects one quarter of the world’s population and causes significant morbidity, including detrimental effects on immune function and cognitive development. Accordingly, the World Health Organization recommends routine iron supplementation in children and adults in areas with high prevalence of iron deficiency. However, a large body of clinical and epidemiological evidence has accumulated which clearly demonstrates that host iron deficiency is protective against falciparum malaria and that host iron supplementation may increase the risk of malaria. Although many effective antimalarial treatments and preventive measures are available, malaria remains a significant public health problem, in part because the mechanisms of malaria pathogenesis remain obscured by the complexities in the relationships between parasite virulence factors, host susceptibility traits, and the immune responses that modulate disease. Here we review (i) the clinical and epidemiological data that describes the relationship between host iron status and malaria infection and (ii) the progress being made to understand the biological basis for these clinical and epidemiological observations.